ISLAMIC GOLD DINAR: THE HISTORICAL STANDARD - Meera, Ahamed Kameel Mydin (Universitas Muhammadiyah Yogyakarta, 2018)
Lately, there have been questions on what the standards for gold dinar and silver dirham should be. Since the dinar and dirham indeed formed the Shari’ah monetary standards from the time of the Prophet pbuh, our work can, therefore, only involve in the rediscovery of that classical standard. Henceforth no parties or organizations can come up with their own standards. Since the Islamic gold dinar[1] did not come into existence until about 50 years after the Prophet’s pbuh demise, it is obvious from history that the solidus of the Eastern Roman Byzantine Empire was the monetary basis for the Shari’ah. Hence the best way to determine the standard is to look at the definition given by its issuer, the Byzantine Empire. Coins unearthed by archeologist cannot be relied upon for this purpose because such coins generally suffer from wear and possible tempering like clipping etc. It was found that the actual historical standard for the dinar to be 4.5gm of pure gold and the dirham to be 3.15gm of pure silver. However, since the role of dinar is simply as a measure of value that depends on the gold-content of the coin and if zakat is based upon 1-year’s provision of foodstuff and not the physical weight of dinars, then the 4.25gm dinar of pure gold and 2.975gm dirham of pure silver, as those circulated during the Prophet’s pbuh era, is the standard since the Prophet had said, “The system of weights and measures is the system of the people of Medina.